The personal archives of Gilda de Mello e Souza and Antonio Candido - Ribas, Elisabete Marin; Escorel, Laura (Revista do Instituto de Estudos Brasileiros, 2020)
Donated to the Institute of Brazilian Studies at the University of São Paulo in 2017, the personal archives of Gilda and Antonio Candido de Mello e Souza will be open to public access in the second half of 2020. The present work aims to share the experience of the technical treatment applied to the teachers' records and to present the content of the funds and some of the research instruments produced, inviting those interested in the life and work of the documentation holders the development of future research.